2010
DOI: 10.1109/led.2010.2064754
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Shunt Leakage in Amorphous Silicon p-i-n Solar Cells

Abstract: Abstract-In this letter, we investigate the nature of shunt leakage currents in large-area (on the order of square centimeters) thin-film a-Si:H p-i-n solar cells and show that it is characterized by following universal features: 1) voltage symmetry; 2) power-law voltage dependence; and 3) weak temperature dependence. The voltage symmetry offers a robust empirical method to isolate the diode current from measured "shunt-contaminated" forward dark IV . We find that space-charge-limited current provides the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…The range of γ was found to be 1 < γ < 2, reflecting the space charge limited transport [23], [24]. The excellent uniformity of the prefactors (G Sh , J 0Sh ) for the measured samples, as summarized in Table I, indicates the process uniformity.…”
Section: A Experimental Observationsmentioning
confidence: 77%
See 2 more Smart Citations
“…The range of γ was found to be 1 < γ < 2, reflecting the space charge limited transport [23], [24]. The excellent uniformity of the prefactors (G Sh , J 0Sh ) for the measured samples, as summarized in Table I, indicates the process uniformity.…”
Section: A Experimental Observationsmentioning
confidence: 77%
“…The P + a-Si emitter and an intrinsic a-Si buffer layer The shunt parameters are extracted from the measured dark I-V data using the method developed in [24]. The n MFB indicate abnormally high ideality factors (n MFB >> 2).…”
Section: A Experimental Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b includes a non-Ohmic shunt current element with power law voltage dependence; i.e. I SH = I SH0 V β , where power exponent β is about 2-3 [8]. Moreover, it has been reported that the magnitude I SH0 at subcell level in TFPV follows a lognormal distribution, as shown in Fig.…”
Section: A Physics and Statistics Of Shunt Currentmentioning
confidence: 96%
“…And, the power exponents and effective mobility µ c are determined by the trap distribution inside the bandgap (characterized by the parameter γ) [8]. These intrinsic shunts are typically formed due to local metal incursion in absorber layers through thin emitter layers, and show similar SCL behavior for different thin film PV technologies [9].…”
Section: Simulation Frameworkmentioning
confidence: 99%